Model Pembelajaran Pendidikan Agama Islam dalam Menanamkan Nilai-nilai Multikultural pada Siswa - Nurtika Syahputri; Syamsu Nahar (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to identify the learning model used in Islamic Religious Education (PAI) lessons to instill multicultural values at SMAS Budisatrya Medan. The research method used is qualitative with a field research approach, data collection techniques in the form of interviews, observations, and documentation. Data analysis is carried out through data reduction, data presentation, data verification, and drawing conclusions. The results of this study indicate that: 1. The learning model that can be utilized in multicultural-based Islamic Religious Education learning is Cooperative Learning. This model allows students to apply group learning, which not only has an impact on cooperative activities, but also on a deep understanding of the material being taught. 2. The efforts of Islamic Religious Education teachers in instilling multicultural values in students have proven effective, where teachers have succeeded in attracting students' interest in better understanding multicultural education and applying it in everyday life. 3. The responses of students of Smas Budisatrya Medan emphasized the importance of tolerance between religious communities in maintaining harmony in schools. They believe that religion teaches to do good to all humans, and they appreciate the school's support in promoting good behavior among students from various religious backgrounds.